Resource allocation algorithm for situation awareness based on multiple-choice quadratic knapsack - Yan-wei SUN; Yun-chuan GUO; Ling-cui ZHANG; Bin-xing FANG (Tongxin xuebao, 2016)
In order to deal with the potential cyber-threat and improve the security situation by using limited resource properly, the optimal allocation of resource focused on cyber security situation. The coherence of network situation lead to the fact that the enhancement of certain item may also affect some other items, and different amount of investment may also result in different degree of impact, therefore, the problem was extracted into the multiple-choice quadratic knapsack problem. The characteristics of quadratic knapsack problem was used to model the interactions among the situation indi-cator items, meanwhile used the multiple choice knapsack problem to model the multiple investment choice for each item. A branch and bound algorithm was conducted by using the semi-definite relaxation. The experiment results show the ac-curacy and efficiency of proposed algorithm.